Buah Mengkudu (Morinda citrifolia L.) Sebagai Pengadsorbi Minyak Jelantah - Barau, Fitri; Nuryanti, Siti; Pursitasari, Indarini Dwi (Jurnal Akademika Kimia, 2015)
The used and storage of cooking oil that has not been done properly can lead to exessive water content in the oil. Thus, this can degrade the quality of the oil and fried foods, and turn to interfere health. The aim of this study was to determine teh quality of used cooking oil after adsorbed by mengkudu or noni (morinda citrifolia L.) powder. The quality of the oil was determined based on the free fatty acids content, peroxide numbers, moisture and dirt content before and after adsorbased by using the titration method in determining the FFA content and peroxide number, while the water content and impurities levels were determined by using a closed oven method. The quality standard of good oil is based on the Indonesian National Standard (SNI), i.e. the maximum free fatty acid content of 0.3%, the maximum peroxide numbers of 2 meq.O2/kg, the maximum water contens of 0.3%, and the impurities level of 1.0%. The result indicated that the quality of used cooking oil before adsorption was not in accordance with the quality standards of oil. The quality of oil improved after adsorption with 5 grams, 10 grams and 15 grams of noni powder of 100 ml waste cooking oil, and the best absorbent numbers, moisture content, and dirt with 15 grams were 0.2%, 2 meq.O2/kg, 0.09%. This is showed that the quality of the used cooking oil to be better after the addition of noni powder served as an adsorbent.